Eletroforese capilar para monitoramento ambiental: avaliação das estratégias de pré-concentração on-line e off-line para analisar contaminantes emergentes em efluentes - Battistin, Thales de Souza [UNIFESP] (2019)
Emerging contaminants are naturally occurring or anthropogenic chemicals that have no control over the environment and have latent ecotoxicity conditions and deleterious effects on human health. Personal products, repellents, medicines, insecticides, among others, that frequently reach the water bodies, are part of these contaminants. N, N-Diethyl-m-toluamide (DEET) and 3-phenoxybenzyl (1RS)-cis, trans-3- (2,2-dichlorovinyl) -2,2-dimethylcyclopropanecarboxylate (permethrin), used as insect repellent and in the treatment of lice infestation, respectively, have been found in aquatic environments. Alongside these, estrogens have also attracted the attention of environmental agencies, especially 17-α ethinyl estradiol, which is a synthetic hormone used as oral contraceptive pills and considered an endocrine disruptor. Due to the low concentration of these compounds found in water, their analysis has been conducted by chromatographic techniques with mass spectrometric detection, which generates high cost and specialized analyst. The development of low cost methods that allow the determination of different classes of contaminants simultaneously with acceptable limits of quantification should be investigated. Additionally, it is worth mentioning that effluents present high estrogenic activity, being observed the presence of high caffeine concentrations, making this compound an important marker of the presence of emerging contaminants. In this sense, this study aimed to evaluate online and offline preconcentration methods for concomitant analysis of DEET, permethrin, 17-α-ethinylestradiol and caffeine, using capillary electrophoresis (CE) and liquid chromatography (HPLC) with ultraviolet and fluorescence detectors. The optimized conditions for HPLC were: column C18, mobile phase ACN / H2O with a 45:55 (v / v) gradient to 8 min, followed by 95: 5 (v / v) up to 18 min, flow rate of 1 mL/min and temperature 25 ± 2 °C, detection by UV at 220 nm and by fluorescence λex = 280 nm and λem = 310 nm. Micellar electrokinetic chromatography (MEKC) mode was used for the separation of caffeine, DEET and permethrin. Separation was conducted in buffer containing 30 mmol L-1 sodium tetraborate and 40 mmol L-1 SDS, pH 9.2; hydrodynamic injection (0.5 psi for 5s); temperature of 25ºC and 15 kV voltage. Both HPLC and CE methods were efficient, separating the compounds and the two permethrin isomers in less than 20 min. Dispersive liquid microextraction (DLLME) was evaluated as off-line preconcentration strategy using chloroform as extractor solvent and acetonitrile as disperser solvent. Recovery was approximately 37% for caffeine, 36% for DEET, 32% for 17-ethinyl estradiol, 81% for cis-permethrin and 97% for trans-permethrin. Stacking strategies were evaluated as online CE pre-concentration: normal mode stacking, amplified field stacking, salt-mediated stacking and sweeping. Stacking strategies were satisfactory, simple to perform and provided 5-7 fold increases for the compounds.